2021
DOI: 10.1158/1541-7786.mcr-20-0188
|View full text |Cite
|
Sign up to set email alerts
|

Adaptor Protein ShcD/SHC4 Interacts with Tie2 Receptor to Synergistically Promote Glioma Cell Invasion

Abstract: Gliomas are characterized by diffuse infiltration of tumor cells into surrounding brain tissue, and this highly invasive nature contributes to disease recurrence and poor patient outcomes. The molecular mechanisms underlying glioma cell invasion remain incompletely understood, limiting development of new targeted therapies. Here, we have identified phosphotyrosine adaptor protein ShcD as upregulated in malignant glioma and shown that it associates with receptor tyrosine kinase Tie2 to facilitate invasion. In h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…For instance, ShcD can bind and promote ligand-independent activation of EGFR, and its expression parallels EGFR hyperphosphorylation in malignant gliomas [220]. ShcD also binds and induces hyperphosphorylation of Tie2 in glioma cells, and it regulates invadopodia formation, FAK signaling, and invasion [221]. ShcD therefore serves as a novel signaling molecule of interest in glioma.…”
Section: Shc Adaptor Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, ShcD can bind and promote ligand-independent activation of EGFR, and its expression parallels EGFR hyperphosphorylation in malignant gliomas [220]. ShcD also binds and induces hyperphosphorylation of Tie2 in glioma cells, and it regulates invadopodia formation, FAK signaling, and invasion [221]. ShcD therefore serves as a novel signaling molecule of interest in glioma.…”
Section: Shc Adaptor Proteinsmentioning
confidence: 99%
“…Notably, several publications have made clear the potential of using brain-like cerebral organoids prepared from human pluripotent stem cells to study GBM tumor formation and invasion in real time [314,315]. Indeed, our groups have recently adopted this system to demonstrate how Tie2 signaling via ShcD promotes the infiltration of GBM tumor cells [221]. Such cerebral organoid and GBM coculture assays could be easily adapted to search for novel pharmacological agents targeting RTK signaling, such as those effective at limiting the migration of cells from GBM tumorspheres into organoids, or those able to reverse cases where the cancer cells have been allowed to penetrate deep into the organoid model prior to beginning treatment.…”
Section: Emerging Areas Of Gbm Investigationmentioning
confidence: 99%
“…In the nervous system, Lee et al, (2006) demonstrated a subpopulation of neoplastic Tie2 + glial cells that could adhere to collagens type I and IV in an Ang1/Tie2-dependent manner, facilitating the process of glial cell invasion and migration [ 95 ]. More substantial evidence that Tie2 signaling may be involved in glioma cell invasion has been shown in a recent study by Tilak et al, (2021) in which the interaction between the receptor Tie2 and the adaptor protein ShcD/ShC4 synergistically promoted invadopodium formation, matrix degradation, and subsequently glioma cell invasion [ 96 ]. It was also demonstrated that the co-expression of Tie2 and ShcD/SHC4 in invasive glioma cells correlated with an increased expression of N-Cadherin [ 96 ], a classical marker of epithelial-to-mesenchymal transition (EMT) in cancer that supports mesenchymal and invasive phenotypes [ 97 ].…”
Section: Role Of Tie2 Expression In Cancer Cellsmentioning
confidence: 99%
“…More substantial evidence that Tie2 signaling may be involved in glioma cell invasion has been shown in a recent study by Tilak et al, (2021) in which the interaction between the receptor Tie2 and the adaptor protein ShcD/ShC4 synergistically promoted invadopodium formation, matrix degradation, and subsequently glioma cell invasion [ 96 ]. It was also demonstrated that the co-expression of Tie2 and ShcD/SHC4 in invasive glioma cells correlated with an increased expression of N-Cadherin [ 96 ], a classical marker of epithelial-to-mesenchymal transition (EMT) in cancer that supports mesenchymal and invasive phenotypes [ 97 ]. Although Tie2 ligands Ang1 and Ang2 both seem to play important roles in Tie2 activation and cancer progression in gliomas, Brunckhorst et al, (2010) previously showed that Ang4 is an equally vital factor promoting glioblastoma progression in a Tie2-dependent manner [ 98 ].…”
Section: Role Of Tie2 Expression In Cancer Cellsmentioning
confidence: 99%
“…However, reports on SHC4 have been limited to studies of melanoma and glioma. High expression of SHC4 promoted the migration and invasion of melanoma cells and glioma cells [ 16 , 17 ]. The function and regulatory mechanism of SHC4 in HCC are still unknown.…”
Section: Introductionmentioning
confidence: 99%